Peran Badan Usaha Milik Desa Dan Dana Desa Pada Pendapatan Asli Desa - sufiati (Insan Cita Bongaya Research Journal, 2022)
This study aims to determine whether the role of Village-Owned Enterprises and Village Funds has an effect on Village Original Income in Barebbo District, Bone Regency. Collecting data using primary data. The population in this study were 51 village officials in the Barebbo District, Bone Regency. The sampling technique uses saturated sampling so that the entire population is used as a sample. Methods of data analysis using multiple regression analysis. The results of this study indicate that the role of Village-Owned Enterprises and Village Funds has an effect on Village Original Income in Barebbo District, Bone Regency.